(untitled) (Medical Forum Monthly, 2022)
Objective: To evaluate the effects of silymarin alone or in combination with rosuvastatin on elevated total cholesterol, Triglycerides, high levels of Low Density lipoproteins and low levels of High Density Lipoproteins. Study Design: Randomized open clinical trial study Place and Duration of Study: This study was conducted at the National Medical Center, Karachi from October 2020 to March 2021 for a period of six months. Materials and Methods: 90 Hyperlipidemic males and females age group 40≥ and ≤75 years were allocated into three groups of 30 subjects each by computer allocated balloting randomization. The Group A subjects were given Tablet Rosuvastatin 10mg OD alone. The Group B subjects were given Tablet Rosuvastatin 10mg OD and Tablet Silymarin 200mg 1× BD. The Group C subjects were advised Tablet Silymarin 200mg 1×BD alone for the period of 3 months. Baseline investigations FLP, LFTS and CPK were done at week 0 and at week 12. There were total three visits of patients, at week 0, at week 6 and at the end of week 12. Results: Rosuvastatin and Silymarin are consistent in decreasing the lipid levels at week 12 when compared with the baseline. Silymarin also shows good result in decreasing liver enzymes and CPK levels significantly. Conclusion: Silymarin shows great potential in decreasing lipid levels of the blood when used alone and in combination with rosuvastatin. It has also shown great results in decreasing liver enzymes when used alone or in combination with rosuvastatin. The results of this study can further be evaluated with bigger sample size.